REPRESENTASI PEWARTA PEREMPUAN PADA RUBRIK CITIZEN REPORTER HARIAN SERAMBI INDONESIA - Ulfa Khairina (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2018)
Citizen journalism is one of the new categories of journalism that makes it easier for the public to disseminate information to the public. Serambi Indonesia is one og the largest media that facilate citizen reporters to share information. The content of Citizen Reporter on Serambi Indonesia is still limited to informing stories from foreign reporters. This study uses the tehnique of documenting articles on Serambi Indonesia. During August 2018, there were 2 (two) articles representing female journalists in writing articles in the citizen reporter rubric of the Serambi Indonesia. The results showed the female reporter article wrote articles covering the value of news, personal documentation, and construction of article writing